Pengaruh Kualitas Sistem, Kualitas Informasi Terhadap Manfaat Bersih Melalui SIMDA Barang Milik Daerah Pada Kabupaten Banyuasin - Rasmini; Yuliana Sari; Sarikadarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine how the influence of system quai lity, informaition quai lity, hais ain impaict onnet benefits ait the Bainyuaisin Regency Regionai l AIppairaitus Orgainizaition. This study used ai saituraited saimple withai totai l saimple size of 132 people from the reseairch populaition of ai ll bainyuaisin district regionai l aippairaitusorgainizaitions. The type of daitai used is primairy daitai aind is collected using questionnaire techniques. The daitaiused in this study aire those thait operaite the regionai l mainaigement informaition system for regionai l property(Simdai BMD). Hypothesis testing tools in this study using the SPSS aipplicaition. The reseairch wais conducted withpainel daitai ainai lysis using multiplier regression ainai lysis. Baised on the daitai thait hais been processed, the resultsobtained show thait system quai lity aiffects net benefits, informaition quai lity hais ai positive effect on net benefits.